Expansion of acai fruit exploration in the Amazon Estuary: The case of the São Joao Batista Community, Municipality of Abaetetuba, Pará (Research, Society and Development, 2022)
This study aims to evaluate the economic analysis of the production chain of açaí in the São João Batista community, municipality of Abaetetuba, Pará, Brazil, through 31 semi-structured and open interviews with açaí producers. This activity generates larger income during of açaí peak season, ranging from R$ 800 up to R$ 1,000 per month during the peak production season (August to October). The selling price of primary producers in the community varies according to the harvest season, showing a low value during peak season (August to October) due to the abundance of açaí fruits offered. Overall, the impact produced of management and cultivation of açaí on the riverside and extractive economy of the Amazon estuary generates great opportunities for employment, income and quality of life for the people of the plains.